Pendapatan Rumah Tangga Petani Padi Di Kampung Noto Harjo Kecamatan Trimurjo Kabupaten Lampung Tengah - Nita Amanda; Supriyadi Supriyadi; Fikri Syahputra (JURNAL WACANA PERTANIAN, 2023)
Farmer household income is influenced by several assets they have. one of them is land. The amount of income that will be obtained from a farming activity depends on several factors that influence it such as land area, production level, worker identity, planting and the efficiency of using labor. This study aims to determine household income in Noto Harjo Village, Trimurjo District, Central Lampung Regency. This research was conducted in Noto Harjo Village, Trimurjo District, Central Lampung. The samples used were 49 respondents with simple random sampling. The analytical method used is farm income analysis, household income analysis. The results showed that: 1) the average income of lowland rice farming was Rp. 7,589,185 per hectare for each planting and the R/C ratio value was 1.8, this value was more than 1, which meant that rice farming in Noto Harjo Village was profitable and feasible to work on. 2) the contribution of on farm rice farming makes the smallest contribution, with on farm income of Rp. 7,589,185 with a contribution of 12.16%, off farm of Rp. 14,695,203 with a contribution to farmers' income of 23.56%. Meanwhile, non farm income contributed the most, namely Rp.40,080,000 with a contribution of 64.26%.